Water, sanitation and hygiene interventions for acute childhood diarrhea: a systematic review to provide estimates for the Lives Saved Tool - Darvesh, Nazia; Das, Jai K.; Vaivada, Tyler; Gaffey, Michelle F.; Rasanathan, Kumanan; Bhutta, Zulfiqar A. (BMC public health, 2017)
Background In the Sustainable Development Goals (SDGs) era, there is growing recognition of the responsibilities of non-health sectors in improving the health of children. Interventions to improve access to clean water, sanitation facilities, and hygiene behaviours (WASH) represent key opportunities to improve child health and well-being by preventing the spread of infectious diseases and improving nutritional status. Methods We conducted a systematic review of studies evaluating the effects of WASH interventions on childhood diarrhea in children 0–5 years old. Searches were run up to September 2016. We screened the titles and abstracts of retrieved articles, followed by screening of the full-text reports of relevant studies. We abstracted study characteristics and quantitative data, and assessed study quality. Meta-analyses were performed for similar intervention and outcome pairs. Results Pooled analyses showed diarrhea risk reductions from the following interventions: point-of-use water filtration (pooled risk ratio (RR): 0.47, 95% confidence interval (CI): 0.36–0.62), point-of-use water disinfection (pooled RR: 0.69, 95% CI: 0.60–0.79), and hygiene education with soap provision (pooled RR: 0.73, 95% CI: 0.57–0.94). Quality ratings were low or very low for most studies, and heterogeneity was high in pooled analyses. Improvements to the water supply and water disinfection at source did not show significant effects on diarrhea risk, nor did the one eligible study examining the effect of latrine construction. Conclusions Various WASH interventions show diarrhea risk reductions between 27% and 53% in children 0–5 years old, depending on intervention type, providing ample evidence to support the scale-up of WASH in low and middle-income countries (LMICs). Due to the overall low quality of the evidence and high heterogeneity, further research is required to accurately estimate the magnitude of the effects of these interventions in different contexts.